2021
DOI: 10.1108/jchmsd-11-2020-0170
|View full text |Cite
|
Sign up to set email alerts
|

Industrial heritage: towards a sustainable adaptive reuse of wheat milling heritage buildings in Jordan

Abstract: PurposeThe purpose of this paper is to present a framework for the adaptive re-use of wheat milling buildings setting in modern urban contexts in Jordan. This paper also aims to highlight the industrial heritage with a focus on wheat milling buildings, which date back to the beginning of the 20th century, as they document and represent significant aspects of the socio-cultural history of Jordan.Design/methodology/approachThe approach to this statement will be through a theoretical investigation into the notion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…From a design point of view, Eyüce and Eyüce (2010) [62] observed that adaptive reuse project development fails to capture and provide an explicitly expressed design process as well as recognized and established methodologies that may serve as a fiducial mark; instead, they seem to be case-specific and require a special approach. This explains the profusion of case-study-based research methodologies [63][64][65][66][67][68]. Following this, Plevoets and Van Cleempoel (2014) [69] investigated adaptive reuse from the unique perspective of the interior architecture (see also [70]), considering how the interior design is anchored within the inner world of every building.…”
Section: Review Of the Adaptive Reuse Literaturementioning
confidence: 99%
“…From a design point of view, Eyüce and Eyüce (2010) [62] observed that adaptive reuse project development fails to capture and provide an explicitly expressed design process as well as recognized and established methodologies that may serve as a fiducial mark; instead, they seem to be case-specific and require a special approach. This explains the profusion of case-study-based research methodologies [63][64][65][66][67][68]. Following this, Plevoets and Van Cleempoel (2014) [69] investigated adaptive reuse from the unique perspective of the interior architecture (see also [70]), considering how the interior design is anchored within the inner world of every building.…”
Section: Review Of the Adaptive Reuse Literaturementioning
confidence: 99%
“…A broad range of visitor events can also be understood as green tourism. (Jafari et al, 2000;Jamhawi et al, 2021). Petra: a Nabatean rock town, is one of the New Seven Wonders of the World, enchanting travelers from all over the world.…”
Section: Introductionmentioning
confidence: 99%